Differential effects of exotic Eurasian wild pigs and native peccaries on physical integrity of streams in the Brazilian Atlantic Forest - Rosa,Clarissa; Passamani,Marcelo; Pompeu,Paulo (PeerJ Preprints, 2018)
Wild pigs (Sus scrofa) native to Eurasia and Africa, are one of the world’s most widely distributed invasive species. Their impacts on terrestrial environments have been well documented, however little is known about effects on aquatic environments. We used standardized physical habitat surveys to compare the use of streams by invasive wild pig and native white-lipped peccaries (Tayassu pecari) and their effects on the physical structure of four first-order streams in the Brazilian Atlantic Forest. Two of the streams were used solely by wild pigs and two by peccaries. Each stream was subdivided by cross-sectional transects into continuous sections, each 10 m in length, where we measured the intensity of use of species and different variables related to the stream physical habitat. Although both species used the streams, wild pigs altered physical and environmental parameters more, and with greater intensity, than the native peccaries. Wild pigs decreased the stream bank angle and the riparian ground cover, leading to local erosion, increase of fine sediments and wet width, and a decrease in stream depth. We recommend studies to evaluate the biological consequences of the alterations caused by introduced wild pigs that should be conducted with population control plans in environments where the pig is invasive.
Keywords: Tayassu pecari; Sus scrofa; Ecosystem Engineer; Feral Hogs; Hotspot